Rational Biological Interface Engineering: Amyloidal Supramolecular Microstructure-Inspired Hydrogel - Xuan, Qize; Wang, Yibing; Chen, Chao; Wang, Ping (Frontiers in Bioengineering and Biotechnology, 2021)
Amyloidal proteins, which are prone to form fibrillar and ordered aggregates in vivo and in vitro, underlie the mechanism for neurodegenerative disorders and also play essential functions in the process of life. Amyloid fibrils typically adopt a distinctive β-sheet structure, which renders them with inherent extracellular matrix (ECM)-mimicking properties, such as powerful mechanical strength, promising adhesion, and antibacterial activity. Additionally, amyloidal proteins are a category of programmable self-assembled macromolecules, and their assembly and consequent nanostructure can be manipulated rationally. The above advantages motivate researchers to investigate the potential of amyloidal proteins as a novel type of hydrogel material. Currently, the amyloid-inspired hydrogel has become an emerging area and has been widely applied in a variety of biomedical fields, such as tissue repair, cell scaffolds, and drug delivery. In this review, we focus on the discussion of molecular mechanisms underlying the hydrogenation of amyloidal proteins, and introduce the advances achieved in biomedical applications of amyloid-inspired hydrogels.